Falopletysmografické reakce na optické podnĕty u muzů s poruchami erektivity - Tichý, P (Ceskoslovenska psychiatrie, 1990)
Using the phalloplethysmographic test, comprising 50 coloured slides of six categories, 50 men with impaired erectivity and a control group of 50 men free from disorders or complaints as regards sexual life were examined. On exposure of slides of heterosexual partner activities positive reactions were recorded in all examined men. Men with impaired erectivity, however, displayed in response to these optic erotic stimuli a lower vasomotor reactivity. These men reacted more frequently positively also to homosexual stimuli and to children. In two men with erectile dysfunction the phalloplethysmographic examination revealed a bisexual orientation, in one a preference of heterosexual child objects, in another eight a quite undefined age differentiation in heterosexual objects.
Keywords: Erotica; Humans; Arousal; lidé středního věku; Erectile Dysfunction; dospělí; Penis; erektilní dysfunkce; lidé; Penile Erection; penis; erekce penisu; erotika; Adult; Plethysmography; Male; Middle Aged; pletysmografie; mužské pohlaví; arousal